Distributed resource allocation for DS-CDMA-based multimedia ad hoc wireless LANs. - Sanjay Lal
Power control in direct sequence code division multiple access (DS-CDMA) systems and power/rate allocation in multirate DS-CDMA based networks is an open and interesting research area which has attracted much attention. However, with a few exceptions, most researchers have emphasized centralized resource allocation algorithms for cellular systems where the base station keeps track of the requirements of the various users and is thus responsible for the management of network resources. Ad hoc wireless local area networks (WLANs), on the other hand, are generally configured as peer-to-peer networks with no centralized hub or controller. Thus resource allocation has to be conducted in a distributed fashion. We address the issue of distributed resource management for multirate DS-CDMA based multimedia WLANs by (1) presenting a distributed resource allocation protocol, known as distributed resource negotiation protocol (DRNP) that builds on the RTS/CTS bandwidth reservation mechanism provided by IEEE 802.111, and provides quality of service (QoS) guarantees through distributed control of resources in DS-CDMA based multimedia WLANs and (2) investigating the performance of various resource allocation schemes within the context of DRNP, in terms of network wide metrics such as overall throughput and blocking rates
Keywords: IEEE 802.111.; QoS guarantees; RTS/CTS bandwidth reservation mechanism; WLAN; Base station; Blocking rates; Cellular systems; Centralized resource allocation algorithms; Direct sequence code division multiple access; Distributed control; Distributed resource allocation protocol; Distributed resource management; Distributed resource negotiation protocol; Multimedia ad hoc wireless LAN; Multirate DS-CDMA.; Multirate DS-CDMA based networks; Network resources management; Network wide metrics; Peer-to-peer networks; Power control; Power/rate allocation; Quality of service; Research; Throughput; Wireless local area networks